Ketamine as an alternative to midazolam co-induction to propofol: a comparative study - Yadav, Rupesh Kumar; Bajracharya, Gautam Ratna; Pokharel, Jeju Nath (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Induction of anesthesia with propofol is known to produce systemic hypotension. Co-induction adds a small dose of other anesthetics to reduce the dose of induction agent to decrease hemodynamic disturbances. The aim of the study was to compare hemodynamic changes associated with Midazolam and ketamine as a coinduction agent with Propofol and to compare induction dose of Propofol following the co-induction. Methods: Fifty adult patients undergoing elective surgery to be performed under general anesthesia were randomized to receive 0.3 mg/kg of Ketamine or 0.03 mg/ kg of Midazolam intravenously as co-induction agent. A minute after administration of co-induction agent, anesthesia was induced with Propofol 40 mg bolus then 10 mg every 10 seconds until the loss of verbal response. The hemodynamic response at 0, 1, 2, 5 minutes respectively and the induction dose of Propofol were noted. Results: The mean arterial pressure heart rates were significantly lower at 1, 2 and 5 minutes in midazolam group. However, mean arterial pressure and heart were within the physiological range in both the groups. Propofol dose requirement for induction between the two groups was similar (p>0.05) but co-induction significantly decreased the induction dose of Propofol as compared to standard recommended dose for induction. Conclusion: Our study showed that hemodynamic variables were maintained within the physiological range with midazolam and ketamine co-induction. However, lesser degree of decrease in mean arterial pressure was seen with ketamine but the heart rate was higher. A similar reduction of induction dose of propofol was achieved with both the drugs. Journal of Society of Anesthesiologists of Nepal 2015; 2(2): 62-66